Corporate Governance toward 5.0: Insights from State-Owned Enterprises in Indonesia - Ade Manggala Hardianto; Dwi Arini Nursansiwi (Shirkah: Journal of Economics and Business, 2024)
Existing research separately examines factors like qualification, tenure, and independence in relation to financial performance, overlooking the potential combined or interactive effects. This research intends to determine the role of the board of directors in addressing future challenges encountered by Indonesian state-owned enterprises. The research methodology involves quantitatively correlating independent and dependent variables, with or without variable control, utilizing nine financial ratios to assess firm conditions. The study utilized secondary data from financial statements and annual disclosures of Indonesian state enterprises from 2009 to 2016. The findings indicated that firstly, the degree, whether with or without control variables, is associated with Return on Asset and Fixed Asset Turnover. Secondly, board tenure, with or without control variables, does not exhibit a correlation with financial performance. Thirdly, the size of the independent board of directors, with control variables, does not correlate with financial performance, whereas without control variables, it is correlated with Net Profit Margin and Cash Ratio. This study introduces a new concept of board performance to predict bankruptcy indicators in companies, considering their Return on Assets (ROA) and Fixed Asset Turnover.